Indústria madeireira mundial e brasileira: o caso Paranaense - Mazzochin, Marinez da Silva (2010)
This study seeks to understand the relationship of the process of capital accumulation in the wood processing industry and its relationship with the production of geographical space. The analysis of such a process takes into account the contradictions inherent in their development process. We seek to understand these contradictions, by pointing the main factors that encouraged the development of modern forestry, based on scientific research, especially in relation to raw material, meeting the industrial needs. It was intended in this work demonstrate the relationship between the various geographical scales as the focal point of socio-spatial training for the consolidation of the timber industry in the state of Parana.